Hearing Loss Rehabilitation and Its Contribution to Cognitive-Linguistic Performance in Healthy Older Adults: A Systematic Review - Francisca Mansilla-Jara; Teresa Julio-Ramos; Álvaro Godoy–Díaz; Daniel Solomons; Igor Cigarroa; David Toloza-Ramirez (Revista de Investigación e Innovación en Ciencias de la Salud)
Introduction. Hearing loss (HL) rehabilitation involves using different hearing technologies, such as hearing aids or cochlear implants. The efficacy of HL rehabilitation strategies and their cognitive benefits has been reported for clinical populations, such as those with mild cognitive impairment or dementia. However, up to date, there is no clarity about the cognitive-linguistic implications of HL rehabilitation for healthy older adults. Therefore, increasing knowledge about its benefits in healthy older people is critical to generating early intervention strategies that could delay the progression to pathological stages.